A thermally conductive flame-retardant composite material with a dual-continuous phase structure and a preparation method thereof

By using expanded graphite as a thermal filler in PVC/EVA bicontinuous phase functional composite materials, the problem of difficulty in achieving both flame retardant and thermal conductivity in the prior art is solved, and the comprehensive effect of high thermal conductivity, flame retardant, low smoke and good mechanical properties is achieved.

CN116285156BActive Publication Date: 2025-03-28NANJING TECH UNIV +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310213084.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-08
Publication Date
2025-03-28
Estimated Expiration
2043-03-08

AI Technical Summary

Technical Problem

The prior art is difficult to achieve both flame retardant and thermal conductivity through bicontinuous phase polymer composites, especially without the use of conventional flame retardants, and the mechanical properties of the composites are poor.

Method used

Expanded graphite is used as the thermally conductive functional filler, combined with polyvinyl chloride (PVC) resin and ethylene-vinyl acetate binary copolymer (EVA) as the matrix material, and PVC/EVA bicontinuous phase functional composite material is constructed through specific feeding sequence and process treatment.

Benefits of technology

The composite material has high thermal conductivity and flame retardant properties at lower thermal filler content, and improves the mechanical properties of the material, meeting the needs of high thermal conductivity, flame retardancy, low smoke and good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116285156B_ABST
    Figure CN116285156B_ABST
Patent Text Reader

Abstract

The invention discloses a heat-conducting flame-retardant composite material with a dual-continuous phase structure and a preparation method thereof. The heat-conducting flame-retardant composite material with a dual-continuous phase structure does not need to use any traditional flame retardant, but only uses a specially selected dual-continuous phase polymer system, plus a specific addition method of a heat-conducting filler, to obtain a functional composite material having flame retardant, heat-conducting functions and good mechanical properties. The heat-conducting flame-retardant composite material with a dual-continuous phase structure of the invention is made of the following raw materials in volume ratio: 30-40 parts of a polyvinyl chloride mixture, 30-40 parts of an ethylene-vinyl acetate binary copolymer, 25 parts of graphite, 0-7.5 parts of a chlorinated polyethylene resin, 0-7.5 parts of a vinyl chloride-vinyl acetate binary copolymer, and 0-7.5 parts of an ethylene-vinyl acetate-polar monomer terpolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer composite material and a preparation method thereof, and more particularly to a heat-conducting flame-retardant composite material with a dual-continuous phase structure and a preparation method thereof. Background Art

[0002] Polymer blending modification technology often uses two or more polymers with different properties. Through mechanical melt blending, solution blending, in-situ polymerization blending and other mixing methods, high-performance polymer alloy materials can be prepared by using the complementary characteristics of the matrix materials involved in the blending. Polymer blending modification technology is a simple and effective method to achieve high performance of polymers. The functional materials prepared by this technology have been widely used in many fields such as electronics, automobiles, construction, and energy. If the polymer blends are simply divided into three situations based on the compatibility of the blending system: ① Completely compatible system: After the two polymer materials are blended, they will form a molecular level of compatibility. The blend is not only homogeneous in the macroscopic, but also in the microstructure. Therefore, it is also called a thermodynamically compatible system. ② Completely incompatible system: Because the compatibility of the two polymer materials is too poor, the prepared polymer blend forms a macroscopic phase separation, resulting in this type of polymer blend having no practical value. ③ Partially compatible system: Another situation is that when two polymer materials are blended, although the blend system is thermodynamically incompatible, due to kinetic reasons, that is, the blend system has high viscosity and the movement speed of molecules or segments is extremely slow, so the thermodynamically unstable state becomes relatively stable, forming a macroscopic homogeneous and submicroscopic heterogeneous system. This is the so-called partially compatible polymer blend system, most polymer blends belong to this category, and it is also the polymer blend system with the most practical application value.

[0003] In addition, in polymer blend systems, compared with the classification method based on compatibility, there is another classification method based on the morphology of each phase formed when multi-component polymers are blended, which can be divided into the following two types: 1. "Sea-island" structure: This is a kind of evolution based on the relationship between seawater and islands in the ocean in people's cognition. Only completely incompatible systems and partially compatible systems can form this "sea-island" structure, and completely compatible systems cannot form a "sea-island" structure. In the "sea-island" structure, the polymer component with a smaller content tends to exist in the continuous phase (the so-called "sea" phase) in the form of a dispersed phase (the so-called "island" phase), just like small islands scattered in the ocean, so it is called a "sea-island" structure. The formation of the "sea-island" structure can be used to modify the polymer matrix. For example, the toughening and modification of the polymer matrix with a "sea-island" structure toughening agent is the most typical example. The toughening agent is used in a small amount and is usually dispersed in the matrix in the form of "islands" to form a "sea-island" structure. 2. Dual-continuous phase structure: The weave structure model of heterogeneous multi-component polymers proposes that when two polymers are blended, a dispersed phase will be formed when the volume fraction of one polymer is below 26%; a continuous phase will be formed when the volume fraction of one polymer is above 74%; whether the polymer with a volume fraction of 26-74% forms a dispersed phase or a continuous phase is related to intermolecular forces, system viscosity, blending temperature and other conditions. If the two polymers involved in the blend are close to equal volume composition ratios, they will tend to form an interpenetrating interwoven network structure. This special polymer blend structure is often called a dual-continuous phase structure.

[0004] In a dual-continuous phase polymer blend system, since the two components form a complementary interpenetrating network structure, the special structure of the dual-continuous phase can be used to prepare polymer materials or polymer composite materials with special properties. An example that has been commercialized and widely used is a polyolefin / thermoplastic elastomer dual-continuous phase polymer blend system, such as polypropylene (PP) / styrene-butadiene thermoplastic elastomer (SBS). In a PP / SBS blend system, three structures can usually be formed according to the volume ratio of the two polymers: 1. SBS toughened and modified PP: In this blend system, PP resin is a continuous phase and SBS is a dispersed phase, in which SBS is used as a rubber-type toughening agent to improve the impact toughness of PP, especially the low-temperature impact strength. In this system, SBS is used as an "island" phase and PP is used as a "sea" phase to form a typical "sea-island". 2. PP reinforced modified SBS: In this blend system, SBS is a continuous phase and PP resin is a dispersed phase. Semi-crystalline, high-strength PP resin is used as a reinforcing agent to improve the mechanical properties of SBS strength, such as tensile strength and tear strength. Especially in the oil-filled SBS system, a large amount of liquid oil additives added to SBS will cause its mechanical properties to drop significantly, while the addition of PP resin can effectively improve the mechanical properties of SBS caused by a large amount of oil filling. This system is also a typical "sea-island" structure. The difference from the above is that PP is used as the "island" phase and SBS is used as the "sea" phase. 3. PP / SBS dual-continuous phase structure: Due to the poor compatibility between PP and SBS, the two cannot form a molecularly compatible homogeneous system. When PP and SBS are close to an equal volume ratio, a dual-continuous phase structure can be formed. Taking the PP / SBS dual-continuous phase as an example, the blending system has both the high strength and high heat resistance of PP resin, and the high elasticity and excellent low temperature resistance of SBS. If functional fillers such as conductive carbon black are added to any of the phases (components), a dual-continuous phase composite material with antistatic or conductive functions can be prepared. Compared with PP / SBS "sea-island" type polymer blends, PP / SBS dual-continuous phase polymer blends can achieve better antistatic or conductive functions at lower carbon black content. This is because no matter whether the conductive carbon black is added to the PP or SBS matrix, the conductivity of the PP / SBS dual-continuous phase polymer blend can be achieved by utilizing the conductivity of any phase of the polymer in the dual-continuous phase structure. At this time, the concentration of the conductive filler is greatly reduced relative to the entire polymer system. In other words, a small amount of conductive carbon black can achieve excellent antistatic or conductive properties of the polymer, and the cost is greatly reduced.The Chinese patent with publication number CN111234347A provides a method for preparing a thermoplastic elastomer with excellent conductive properties by combining prefabricated masterbatch with phase structure regulation. The method cleverly designs and regulates that the thermoplastic elastomer SBS is not completely compatible with polyolefin resin (high-density polyethylene, polypropylene) and the blend presents a dual-continuous phase structure when the volume ratio difference between the two is less than or equal to 10%. By pre-adding conductive fillers to any one phase of the polymer and forming a conductive path, the amount of conductive fillers used is greatly reduced, and the conductive properties of the polymer composite material are significantly improved.

[0005] Although dual-continuous phase polymer blends have some advantages, especially in the preparation of composite materials with antistatic or conductive functions, the amount of conductive filler can be reduced. However, in order to enable the polymer blend to form a dual-continuous phase structure, there are many factors that affect the formation of the dual-continuous phase polymer structure, such as the type of polymer, the content of the polymer, the molecular weight, the compatibility, etc., which are all factors that should be considered, and compatibility is one of the most important factors. Since the compatibility between the polymer types forming the dual-continuous phase cannot be too good, the mechanical properties of the dual-continuous phase polymer blends formed are often poor. Therefore, the preparation of functional composite materials with good mechanical properties and other characteristic functions (such as flame retardant, conductive, thermal conductive, etc.) is to further expand the use of functional composite materials and is a new demand of the industry. For example, the Chinese patent with the publication number CN111234347A successfully prepared a PP / SBS dual-continuous phase polymer composite material with low carbon black content and high conductive (antistatic) performance, but the PP / SBS dual-continuous phase polymer system is difficult to achieve other functions such as flame retardant and thermal conductive. In particular, it is very difficult to prepare flame-retardant composite materials using PP / SBS dual-continuous phase polymers. This is because both PP resin and SBS elastomer only contain C and H in their molecular structure, and their limiting oxygen index (LOI) is between 16% and 19%, which is a typical flammable polymer. If a flame retardant is added to any of the phases, it is almost impossible to achieve flame retardant properties of the PP / SBS system through the special structure of the dual-continuous phase.

[0006] In summary, the existing technology for preparing composite materials with single functions of flame retardancy and thermal conductivity or multifunctional composite materials with flame retardancy and thermal conductivity using dual-continuous phase structure polymer materials has certain limitations. If it is possible to avoid using halogen flame retardants, phosphorus flame retardants, nitrogen flame retardants, and inorganic flame retardants (magnesium hydroxide, aluminum hydroxide, etc.) commonly used in the preparation of flame-retardant polymers in the prior art, by constructing dual-continuous phase polymer materials with special structures and making them have flame retardancy and thermal conductivity functions at the same time, and also have good mechanical properties, it can enrich the existing preparation of dual-continuous phase polymer composite materials and meet the specific needs of the market. Summary of the invention

[0007] The purpose of the present invention is to solve the problems and shortcomings of the prior art in preparing a dual-continuous phase polymer composite material, and to provide a thermally conductive flame-retardant composite material with a dual-continuous phase structure. The composite material does not need to use any traditional flame retardant, but only uses a specially selected dual-continuous phase polymer system, plus a specific addition method of a thermally conductive filler, to obtain a functional composite material having flame retardancy, thermal conductivity and good mechanical properties. The present invention selects expanded graphite as a thermally conductive functional filler, polyvinyl chloride (PVC) resin and a ethylene-vinyl acetate binary copolymer (EVA) of a specific structure as a matrix material, and constructs a PVC / EVA dual-continuous phase functional composite material by a special method of mixing expanded graphite with EVA resin first and then blending with PVC. PVC resin is an amorphous thermoplastic resin prepared by polymerization reaction with vinyl chloride as a monomer, and has excellent weather resistance, flame retardancy, mechanical properties and electrical insulation. The chlorine atomic mass percentage in PVC resin is as high as 56%, so the limiting oxygen index of PVC resin exceeds 45%, and it is a polymer variety with excellent flame retardancy. However, the non-crystallization of PVC resin makes its thermal conductivity poor. The thermal conductivity of PVC at room temperature is only about 0.17-0.18 W·m -1 ·K -1 . Compared with crystalline polymers, the non-crystalline nature of PVC resin makes it very difficult to prepare high thermal conductivity functional materials. The matrix thermal conductivity of EVA resin is related to factors such as the polymerization method, the sequence structure of the EVA macromolecular main chain, and the vinyl acetate (VAc) content. Usually, block copolymers can maintain the properties of their respective homopolymers, especially the high crystallinity of the polyethylene block, which makes the block copolymer EVA resin have a higher thermal conductivity. The random copolymer main chain structure destroys the regular structure of the polyethylene chain, resulting in a lower thermal conductivity of the random copolymer EVA resin. Since commercialized EVA resins are all random copolymer structures, the higher the VAc content and the relatively fewer regular polyethylene segments in the EVA resin, the lower the overall crystallinity of the EVA resin, which ultimately leads to a decrease in its thermal conductivity. In studying the relationship between VAc content, crystallinity and thermal conductivity of EVA resin, we found that when the mass percentage of comonomer VAc is between 5% and 20%, EVA resin is a typical semi-crystalline polymer with relatively high crystallinity (20% to 35% as measured by differential scanning calorimetry (DSC)) and high thermal conductivity (0.30 to 0.34 W·m -1 ·K -1), especially the block copolymer EVA resin has a higher thermal conductivity. Since the thermal conductivity of EVA resin with medium and low VAc content is significantly higher than that of PVC resin, adding thermal conductive functional filler expanded graphite to the EVA matrix resin is more beneficial for preparing a composite material with high thermal conductivity. In addition, the limiting oxygen index of EVA resin is 19-21%, which is a typical flammable polymer. If the thermal conductive functional filler expanded graphite is first dispersed in the EVA matrix resin and then blended with the PVC resin, the flame retardant properties of the EVC resin can be greatly improved, so that the limiting oxygen index of the PVC / EVA dual-continuous phase functional composite material exceeds 35%, and the vertical burning test is V-0 level, which is a typical high flame retardant polymer material.

[0008] The PVC / EVA dual-continuous phase functional composite material of the present invention has the characteristics of good thermal conductivity, flame retardancy, etc. At the same time, in order to further improve the compatibility of the PVC / EVA dual-continuous phase, chlorinated polyethylene resin (CPE), vinyl chloride-vinyl acetate binary copolymer (VC-co-VAc), and ethylene-vinyl acetate-polar monomer terpolymer are selected as compatibilizers, and the mechanical properties of the PVC / EVA dual-continuous phase polymer composite material are effectively improved while keeping the thermal conductivity and flame retardancy unchanged.

[0009] The present invention also provides a method for preparing the heat-conductive flame-retardant composite material with a dual-continuous phase structure. The method is simple and easy to implement and can prepare a PVC / EVA dual-continuous phase functional composite material with good flame retardancy, high thermal conductivity and excellent mechanical properties.

[0010] The present invention is achieved through the following technical solutions:

[0011] The heat-conductive flame-retardant composite material with a dual-continuous phase structure of the present invention is made of the following raw materials in volume ratio:

[0012]

[0013] The thermally conductive flame-retardant composite material with a dual-continuous phase structure of the present invention has a further technical solution that the polyvinyl chloride mixture is made of the following raw materials in the following mass ratio:

[0014]

[0015]

[0016] A further technical solution is the thermally conductive flame-retardant composite material with a dual-continuous phase structure, characterized in that the polyvinyl chloride resin is a powdered resin with an average degree of polymerization of 1000 or a combination of 1000 and 1300 synthesized by a suspension polymerization process, wherein the mass proportion of the polyvinyl chloride resin with an average degree of polymerization of 1300 does not exceed 50% when combined. PVC is a typical amorphous resin, and its own thermal conductivity is low, and the thermal conductivity is only 0.17 W·m at 20°C. -1 ·K -1 , the thermal conductive functional filler is selectively dispersed in the semi-crystalline EVA resin, and the composite material has better thermal conductivity. In order to better control the PVC and EVA systems to form their own continuous phases, the viscosity of the PVC resin with an average degree of polymerization of 1000, 1300 or a combination thereof is equivalent to that of the EVA / graphite blending system, and it is easier to form a dual continuous phase structure. If all polyvinyl chloride resins with an average degree of polymerization of 1300 or a higher proportion of polyvinyl chloride resins with an average degree of polymerization of 1300 are used, there are processing difficulties due to the lack of plasticizers.

[0017] The above-mentioned heat-conducting flame-retardant composite material with a dual continuous phase structure of the present invention can also be further technically solved in that the ethylene-vinyl acetate binary copolymer (EVA) is a random copolymer or block copolymer of ethylene and vinyl acetate with a vinyl acetate (VAc) mass percentage of 5-20% and a melt mass flow rate of (190°C×2.16kg) 10-20g / 10min. The matrix thermal conductivity of EVA resin is related to factors such as the polymerization method, the sequence structure of the EVA macromolecular main chain, and the VAc content. Generally, block copolymers can maintain the properties of their respective homopolymers, especially the high crystallinity of the polyethylene block, which makes the block copolymer EVA resin have a higher thermal conductivity. The random copolymer main chain structure destroys the regular structure of the polyethylene chain, resulting in a lower thermal conductivity of the random copolymer EVA resin. Taking copolymerized EVA resin as an example, the higher the VAc content, the fewer regular polyethylene segments in the EVA resin, and the lower the overall crystallinity of the EVA resin, which ultimately leads to a decrease in its thermal conductivity, among which the thermal conductivity of the random copolymerized EVA resin decreases more. The selection of EVA resin with a VAc mass percentage of 5 to 20% is based on the consideration that this type of EVA matrix resin has a high crystallinity and a corresponding high thermal conductivity, and adding a thermal conductive functional filler is more beneficial to the preparation of a composite material with high thermal conductivity, wherein the selection of block copolymerized EVA resin will have a higher thermal conductivity; the selection of a high-flowability EVA resin with a melt mass flow rate (190°C×2.16kg) of 10 to 20g / 10min is based on the consideration that after adding a large amount of thermal conductive fillers, it can still maintain good processing flowability, and is easier to form a dual continuous phase when blended with a PVC mixture. A further technical solution is that the ethylene-vinyl acetate binary copolymer is preferably a powdered ethylene-vinyl acetate binary block copolymer.

[0018] The thermally conductive flame-retardant composite material with a dual-continuous phase structure of the present invention can also be further technically provided that the graphite is a high-purity expanded graphite, wherein the carbon mass percentage of the high-purity expanded graphite is 99.5% or more, the sheet thickness is 0.1 to 0.2 μm, the sheet length is 20 to 30 μm, the expansion volume is 250 to 300 mL / g, and the specific surface area is 25 to 30 m 2 / g.

[0019] The above-mentioned heat-conducting flame-retardant composite material with a dual-continuous phase structure of the present invention can also be further technically provided that the chlorinated polyethylene (CPE) resin is a high-fluidity variety with a chlorine atomic mass percentage of 30-40%, a melting heat of 15-25 J / g, and a melt mass flow rate (190°C×2.16kg) of 30-40 g / 10min, and the amount of the chlorinated polyethylene resin is 2.5-7.5 parts. Compared with typical non-polar polymer polyethylene resins, the mechanical properties of the dual-continuous phase polymer alloy prepared by blending EVA resin with a certain polarity with PVC resin are better than those of the PVC / PE blending system, but since the EVA resin with a medium-low VAc content is selected to blend with PVC under the consideration of thermal conductivity, if the compatibility of the two is further improved, the mechanical properties will be further improved, which is more conducive to practical application. Chlorinated polyethylene (CPE) resin is made by using high-density polyethylene through a random chlorination process of aqueous suspension. The unchlorinated part of its structure still retains the segment part of polyethylene resin, and the structure of the part that undergoes chlorination reaction is the same as that of PVC resin. Therefore, CPE resin is a copolymer of ethylene and vinyl chloride from a structural analysis. Selecting CPE resin with a chlorine atomic mass percentage of 30-40% can effectively increase the capacity of the PVC / EVA blend system and improve the mechanical strength to meet the actual use requirements. In addition, the CPE resin with high melting heat retains more polyethylene long chains in its main chain structure, and has good compatibility with EVA resin (especially with block structure EVA resin; the CPE resin with high melting heat also shows that more polyethylene crystal regions are retained in its structure, which is more conducive to the preparation of dual-continuous phase composite materials with excellent thermal conductivity. The use of high-fluidity CPE resin is conducive to overcoming the deficiency of reduced fluidity caused by flake graphite thermal conductive filler and improving the processing performance of composite materials.

[0020] The above-mentioned heat-conducting flame-retardant composite material with a dual-continuous phase structure of the present invention can also be further technically solved by the following method: the vinyl chloride-vinyl acetate binary copolymer (VC-co-VAc) is a copolymer prepared by a suspension process with a VAc mass percentage of 15-30%, an average polymerization degree of 400-600, and vinyl chloride (VC) and vinyl acetate, and the amount of the vinyl chloride-vinyl acetate binary copolymer is 2.5-7.5 parts. The vinyl chloride-vinyl acetate binary copolymer is selected based on improving the compatibility of the dual-continuous phase of PVC / EVA, and a part of the vinyl chloride segment in the main chain of the vinyl chloride-vinyl acetate binary copolymer (VC-co-VAc) is the same as the main chain of the PVC resin, and another part of the vinyl acetate segment is the same as the vinyl acetate segment of the EVA resin. Therefore, structurally analyzing vinyl chloride-vinyl acetate binary copolymer is a compatibilizer of typical incompatible PVC / EVA blending system, selecting vinyl chloride-vinyl acetate binary copolymer with 15-30% VAc mass percentage, VAc content in its structure is close to VAc content in EVA, can effectively improve the interfacial adhesion of PVC / EVA blending system, improve mechanical strength. Of course, if CPE and VC-co-VAc are used in combination to increase the capacity of PVC / EVA blending system, the effect is better, this is because in PVC / EVA blending system, three kinds of monomer units are contained, namely, vinyl chloride, ethylene and vinyl acetate, and the compatibilizer, whether CPE (containing only two kinds of monomer units of vinyl chloride and ethylene in its structure) or VC-co-VAc (containing only two kinds of monomer units of vinyl chloride and vinyl acetate in its structure), only contains two kinds of the above three kinds of monomer units, and CPE and VC-co-VAc compounding compatibilizer contain the same three kinds of monomer units (vinyl chloride, ethylene and vinyl acetate) in PVC / EVA blending system.

[0021] The thermally conductive flame-retardant composite material with a dual continuous phase structure of the present invention can also be further technically provided that the ethylene-vinyl acetate-polar monomer terpolymer is an ethylene-vinyl acetate-carbon monoxide terpolymer or an ethylene-vinyl acetate-acrylate terpolymer, and the amount thereof is 2.5-7.5 parts. Commercial varieties include Elvaloy 741, Elvaloy 742, Elvaloy 837, Elvaloy 838, etc. of DuPont.

[0022] The method for preparing the thermally conductive flame-retardant composite material having a dual-continuous phase structure of the present invention comprises the following steps:

[0023] Premixing of EVA and graphite: Add ethylene-vinyl acetate binary copolymer, i.e. EVA, to a common low-speed mixer, and then add chlorinated polyethylene resin, i.e. CPE, vinyl chloride-vinyl acetate binary copolymer, i.e. VC-co-VAc, or ethylene-vinyl acetate-polar monomer terpolymer according to the proportion, start the low-speed mixer and mix at room temperature for 2-3 minutes, add graphite and continue mixing for 5-6 minutes to obtain the EVA and graphite premix, wherein the material temperature is controlled not higher than 40°C and the speed is controlled not higher than 450rpm during the whole mixing process;

[0024] EVA / graphite composite melt blending: EVA and graphite premixes were pelletized by underwater pelletizing in a parallel twin-screw extruder to prepare EVA / graphite composite pellets, wherein the screw diameter was 65 mm and the screw aspect ratio L / D was 32:1; twin-screw extruder pelletizing molding control conditions: zone 1 temperature 120±10℃, zone 2 temperature 135±10℃, zone 3 temperature 150±10℃, zone 4 temperature 160±10℃, zone 5 temperature 150±10℃, die head temperature 200±10℃; circulating water temperature 55±5℃;

[0025] Preparation of polyvinyl chloride mixture and premixing with EVA / graphite composite material: add PVC resin, organic tin stabilizer and calcium stearate to a high-speed mixer and mix at a low speed of 400-450rpm for more than 2 minutes, start high-speed 900-950rpm to mix until the temperature reaches 90°C, add acrylate processing aid, continue mixing and heat to 100°C of the polyvinyl chloride mixture, add polyethylene wax and mix for another 2-3 minutes, and then discharge the material into a low-speed mixer with jacket circulating cooling water; when the material is cooled to 60°C, add EVA / graphite composite material pellets, continue mixing until the temperature reaches 40±5°C and discharge the material into a storage bin;

[0026] Preparation of thermally conductive flame-retardant composite materials with a dual-continuous phase structure: the materials in the storage bin are processed by a parallel co-rotating twin-screw extruder with a screw diameter of 65 mm and an aspect ratio of 36:1, including blending, underwater drawing and pelletizing, to obtain a thermally conductive flame-retardant composite material with a dual-continuous phase structure; the extruder granulation molding control conditions are: zone 1 temperature 150±5℃, zone 2 temperature 160±5℃, zone 3 temperature 170±5℃, zone 4 temperature 180±5℃, zone 5 temperature 180±5℃, zone 6 temperature 170±5℃, head temperature 160±5℃; main engine screw speed 40±5rpm, feeding speed 20±2rpm, pelletizing speed 200±10rpm.

[0027] Since the thermal conductivity of semi-crystalline EVA resin with a VAc mass percentage of 5 to 20% is between 0.30 and 0.34 W·m -1 ·K -1It is significantly higher than the 0.17 W·m of amorphous PVC resin. -1 ·K -1 If the thermal conductive filler is first added to the EVA resin and then blended with the PVC mixture to prepare the dual-continuous phase composite material, the thermal conductivity will be greater than the thermal conductivity of the dual-continuous phase composite material prepared by first adding the thermal conductive filler to the PVC mixture and then blending with the EVA resin. In addition, since the limiting oxygen index of EVA resin is only about 20%, it is very flammable in the air, while the PVC molecular structure contains 56% of chlorine atoms and the limiting oxygen index is as high as 45% or more, and it is a flame-retardant polymer with excellent flame retardant properties in the air. Adding the thermal conductive filler to the EVA resin first can effectively reduce its limiting oxygen index and improve the flame retardant properties. At this time, the flame retardant properties of the dual-continuous phase composite material prepared by blending with the PVC mixture are further improved.

[0028] Limiting oxygen index test method: The oxygen index meter (model: JF-3) produced by Nanjing Jiangning Analytical Instrument Co., Ltd. is used to evaluate the flame retardant properties of the sample. According to GB / T 2406.2-2009 standard, the limiting oxygen index refers to the volume fraction concentration of oxygen in a mixture of oxygen and nitrogen when the polymer can just support its combustion, expressed as the volume percentage of oxygen. The size of the sample is 80mm×10mm×4mm. The sample is ignited by the top surface ignition method, and the flame is applied for 30s. The sample is removed every 5s to observe the burning state. After the top surface of the sample continues to burn, the igniter is removed. At this time, the sample is ignited and the burning time and the burning length are recorded to determine the limiting oxygen index value of different samples.

[0029] Test method for building material smoke density: According to GB / T 8627-2007 standard, the test is carried out on the building material smoke density tester (model: JCY-3A) produced by Nanjing Jiangning Analytical Instrument Co., Ltd. to evaluate the smoke density of the sample when it is burning. Before the test, the instrument needs to be calibrated with a filter and the flame position is determined. The test sample is placed horizontally on the bracket, and its position should be directly above the flame after the igniter is in place. Burn for 4 minutes under propane gas with a pressure of 276KPa. Each group of samples is tested 3 times and the average value is taken. The smoke density level and maximum smoke density of different samples can be obtained through the curve of the light absorption rate and time of the sample. The highest point of the curve is the maximum smoke density. The area enclosed by the curve and the time axis, divided by the total area of ​​the curve, and then multiplied by 100, is the smoke density level of the sample.

[0030] Vertical combustion test method: According to the US UL-94 standard, the horizontal vertical combustion tester (model: CZF-4) produced by Nanjing Shangyuan Analytical Instrument Co., Ltd. is used to conduct vertical combustion test of the sample. The sample is placed vertically, and the lower end of the sample is ignited with a flame of a specified height for 10 seconds. The time of flame burning of the sample after leaving the fire is recorded. After the flame of the sample is extinguished, the flame is ignited again, and the burning time is recorded. Repeat 5 times and the total cumulative burning time is used to determine the flame retardant grade. The sample size is 130mm×13mm×2mm.

[0031] Thermal conductivity test method: The thermal conductivity of the sample was tested using a thermal conductivity meter (model: TC3000E) from Xi'an Xiaxi Technology. The test method was the hot wire method and the test standard was ASTM C1113. Each group of samples was tested 5 times and the average value was taken. The interval between each test was 10 minutes, and the test voltage and test time were 1.5V and 5s, respectively. The test environment was 23°C. Thermal balance control was performed before each test. The thermal conductivity test was performed when the temperature fluctuation was less than ±0.1K. The sample size was 50mm×40mm×4mm. The samples for isotropic thermal conductivity tests were prepared using a dual-continuous phase PVC / EVA composite material through an injection molding process, and the samples for anisotropic thermal conductivity tests were prepared using a dual-continuous phase PVC / EVA composite material through a single screw extrusion molding process.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention overcomes the prior art of preparing a dual-continuous phase polymer blend, mainly targeting the following deficiencies of dual-continuous high flame retardant and high thermal conductivity functional composite materials, and selectively selects polymer materials, especially through special processes such as formula design and addition sequence, and creatively improves them: ① Although PVC is a typical amorphous resin, its own thermal conductivity is relatively low, and its thermal conductivity is only about 0.17-0.18 W·m at 20°C -1 ·K -1, it is difficult to prepare functional materials with low filler content and high thermal conductivity. If the thermal conductive functional filler is first selectively dispersed in the semi-crystalline EVA resin and then blended with PVC to form a special dual-continuous phase structure, the composite material can achieve high thermal conductivity at a low thermal conductive filler content. ②The matrix thermal conductivity of EVA resin is related to factors such as the polymerization method, the sequence structure of the EVA macromolecular main chain, and the VAc content. Usually, block copolymers can maintain the properties of their respective homopolymers, especially the high crystallinity of the polyethylene block, which makes the block copolymer EVA resin have a higher thermal conductivity. Compared with block copolymer EVA resin, the VAc segment in the main chain structure of random copolymer EVA resin destroys the regular structure of the polyethylene chain, resulting in a lower thermal conductivity. Whether it is a block copolymer EVA resin or a random copolymer EVA resin, the higher the VAc content in its structure and the relatively fewer regular polyethylene segments in the EVA resin, the lower the overall crystallinity of the EVA resin, which ultimately leads to a decrease in its thermal conductivity. Among EVA resins with the same VAc content, the thermal conductivity of random copolymerized EVA resin decreases more significantly. The preferred block copolymerized EVA matrix resin will have a higher thermal conductivity, and the obtained PVC / EVA dual-continuous phase composite material will also have a higher thermal conductivity accordingly. ③ The selection of powdered EVA resin to be mixed with expanded graphite first has the following advantages: the powdered EVA resin can be more easily dispersed in advance with the powdered expanded graphite before melt processing, which is beneficial to the next step of melt mixing processing. The powdered EVA resin can be mixed evenly with the powdered expanded graphite in ordinary low-speed mixing equipment, avoiding the destruction of the high diameter-to-thickness ratio structure of the expanded graphite caused by the use of high-speed mixing equipment. Powdered EVA is easier to plasticize, and it is convenient to quickly mix evenly with the expanded graphite with a high specific surface area; the powdered EVA with a high melt flow rate has a lower melt viscosity after rapid plasticization at high temperature, and will not destroy its special high sheet diameter ratio structure when melt-mixed with expanded graphite at high temperature. ④ The special semi-crystalline EVA resin with a mass percentage of 5-20% of the comonomer VAc has a relatively high crystallinity (20-35%) and a high thermal conductivity (0.30-0.34 W·m -1 ·K -1) characteristics, and at the same time designed a method of first adding high-purity expanded graphite to EVA resin and then blending it with PVC resin to obtain a dual-continuous phase PVC / EVA with thermal conductivity that is much better than the thermal conductivity of dual-continuous phase PVC / EVA obtained by first adding high-purity expanded graphite to PVC resin and then blending it with EVA resin, or by blending PVC resin and EVA resin evenly and then adding high-purity expanded graphite. ⑤ Compared with EVA, polyethylene has a higher degree of crystallinity and a larger thermal conductivity. For example, the crystallinity of high-density polyethylene (HDPE), medium-density polyethylene (MDPE), and low-density polyethylene (LDPE) are approximately 65%, 55%, and 40%, respectively, and the corresponding thermal conductivity is approximately 0.40 W·m -1 ·K -1 , 0.36W·m -1 ·K -1 , 0.34W·m -1 ·K -1 Therefore, if polyethylene is selected as the matrix material and thermal conductive fillers are first added and then blended with PVC to prepare the co-continuous phase, it should have a higher thermal conductivity. However, since polyethylene and polyvinyl chloride are two typical non-polar and highly polar polymers, their solubility parameters are approximately 16.5 (J.cm -3 ) 1 / 2 、20.0(J.cm -3 ) 1 / 2 , the polarity difference between the two is too great, and the mechanical properties of the dual-continuous phase PVC / PE composite material formed after blending are very poor, and it has no practical value. ⑥ Compared with polyethylene, the vinyl acetate copolymer unit structure introduced into the EVA structure contains polar ester groups, which leads to an increase in the polarity of the EVA molecule and a certain degree of improvement in its compatibility with PVC. The polarity and solubility parameter of EVA are related to the VAc content, and its solubility parameter is usually between 17.5 and 19.5 (J.cm -3 ) 1 / 2The higher the VAc content in the EVA structure and the more polar the molecules are, the better the compatibility with PVC. However, with the increase of VAc, the crystallinity of the copolymer EVA resin decreases, and the thermal conductivity of the matrix resin also decreases. If an EVA matrix resin with a high VAc content is selected, although it is beneficial to improve the mechanical properties, it is not conducive to the preparation of high thermal conductivity composite materials. Only by selecting EVA resins with medium and low copolymer monomers VAc, such as semi-crystalline EVA resins with a VAc mass percentage of 5 to 20%, can it meet the premise of having a certain compatibility with PVC resin and having a relatively high thermal conductivity. ⑦ Considering that the thermal conductive filler expanded graphite needs to be pre-dispersed in the EVA matrix resin, in order to better control the PVC and EVA systems to form their own continuous phases, the viscosity matching of the two-phase system at high temperature is very important. The selection of high-flowability EVA resin with a melt mass flow rate (190℃×2.16kg) of 10-20g / 10min is based on the consideration that after adding a certain amount of thermal conductive filler, it can still maintain good processing flowability and is easier to form a dual-continuous phase when blended with PVC mixture.⑧ In the non-plasticized PVC system, the selection of PVC resin with an average degree of polymerization of 1000, 1300 or a combination thereof is also to ensure that its viscosity is high, and at the same time, it is equivalent to the viscosity of the EVA / graphite blending system, and it is easier to form a dual-continuous phase structure. However, if all polyvinyl chloride resins with an average degree of polymerization of 1300 or a higher proportion of polyvinyl chloride resins with an average degree of polymerization of 1300 are used, there are processing difficulties due to the lack of plasticizers. ⑨EVA resin is a type of flammable polymer. The traditional method for preparing flame-retardant EVA is to add halogen flame retardants, phosphorus flame retardants, nitrogen flame retardants, inorganic flame retardants (magnesium hydroxide, aluminum hydroxide, etc.) and other flame retardants to its matrix resin system. The present invention takes a unique approach to utilize the thermal conductive filler expanded graphite to first add to the EVA resin to obtain high thermal conductivity while appropriately improving the flame retardant properties of EVA, and then blend it with a non-plasticized PVC resin with a chlorine atomic mass percentage of up to 56% and a limiting oxygen index of more than 45%. The resulting high thermal conductivity PVC / EVA composite material with a dual-continuous phase structure has a limiting oxygen index of more than 35%, a vertical combustion test reaching V-0 level, a smoke density level of ≤50%, and a maximum smoke density of only about 70-80%, which is much lower than the functional material prepared with PVC resin as the matrix. ⑩ Although compared with the typical non-polar polymer polyethylene resin, the mechanical properties of the dual-continuous phase polymer alloy prepared by blending EVA resin with a certain polarity with PVC resin are better than those of the PVC / PE blending system. However, due to the consideration of thermal conductivity, only EVA resins with medium and low VAc contents (not as good as EVA resins with high VAc contents) can be selected for blending with PVC. If the compatibility of the two is further improved, the mechanical properties will be further improved, which is more conducive to practical application.The invention selects to add a small amount of chlorinated polyethylene resin, vinyl chloride-vinyl acetate binary copolymer, and ethylene-vinyl acetate-polar monomer terpolymer, which can effectively improve the mechanical properties of the blend without affecting the thermal conductivity and flame retardancy of the PVC / EVA dual-continuous phase composite material. Since chlorinated polyethylene (CPE) resin is made by random chlorination process of high-density polyethylene through water phase suspension, the unchlorinated part of its structure still retains the segment part of polyethylene resin, and the structure of the part that undergoes chlorination reaction is the same as that of PVC resin. Therefore, CPE resin is equivalent to a copolymer of ethylene and vinyl chloride from a structural analysis. Selecting CPE resin with a chlorine atomic mass percentage of 30-40% can effectively increase the capacity of PVC / EVA blending system and improve mechanical strength to meet actual use requirements. In addition, CPE resin with high melting heat retains more polyethylene long chains in its main chain structure, and has good compatibility with EVA resin, especially with block structure EVA resin; CPE resin with high melting heat also shows that more polyethylene crystal regions are retained in its structure, which is more conducive to the preparation of dual-continuous phase composite materials with excellent thermal conductivity. The use of CPE resin with high fluidity is conducive to overcoming the deficiency of decreased fluidity caused by flake graphite thermal conductive filler, and also has a certain effect of improving the processing performance of composite materials. The selection of vinyl chloride-vinyl acetate binary copolymer (VC-co-VAc) is also based on improving the compatibility of PVC / EVA dual continuous phases. The vinyl chloride segment part in the main chain of vinyl chloride-vinyl acetate binary copolymer is the same as the main chain structure of PVC resin, and the other part of the vinyl acetate segment is the same as the vinyl acetate segment of EVA resin. Therefore, from a structural analysis, vinyl chloride-vinyl acetate binary copolymer is a compatibilizer for typical PVC / EVA blending system. Selecting vinyl chloride-vinyl acetate binary copolymer with a VAc mass percentage of 15 to 30% can effectively improve the interfacial adhesion of the PVC / EVA blending system and improve the mechanical strength. If CPE and VC-co-VAc are used together, they have a synergistically enhanced compatibilization effect on the PVC / EVA blend system. This is because the polymer main chain in the PVC / EVA blend system contains three monomer units, namely vinyl chloride, ethylene and vinyl acetate, and the compatibilizer, whether CPE (whose structure contains only two monomer units, vinyl chloride and ethylene) or VC-co-VAc (whose structure contains only two monomer units, vinyl chloride and vinyl acetate), only contains two of the above three monomer units. The CPE and VC-co-VAc compound compatibilizer contains the same three monomer units as the polymer in the PVC / EVA blend system: vinyl chloride, ethylene and vinyl acetate. Therefore, the synergistic compatibilization effect of CPE and VC-co-VAc is more significant. Selecting one of the ethylene-vinyl acetate-polar monomer terpolymers, such as ethylene-ethylene-vinyl acetate-carbon monoxide terpolymer, ethylene-vinyl acetate-acrylate terpolymer, etc., has a good effect on the compatibilization of the PVC / EVA blend system. This is because the monomer units such as ethylene, vinyl acetate, and a polar third monomer (carbon monoxide, acrylate, etc.) in this type of ternary copolymer resin correspond to the same three monomer units in the PVC / EVA blend system: ethylene, vinyl acetate, and vinyl chloride. A compatibilizer with a relatively low molecular weight or a relatively high melt mass flow rate is selected to be first mixed with the EVA resin and then melt-blended with graphite to prepare EVA / graphite composite material pellets. This has the advantages of further lowering the melt viscosity of the EVA / graphite composite material and improving fluidity. It is also beneficial to improve the compatibility with the PVC resin. The prepared dual-continuous phase PVC / EVA functional composite material has better mechanical properties.

[0034] In summary, the thermally conductive flame-retardant composite material with a dual-continuous phase structure is a PVC and EVA matrix material, and a high-purity, high-diameter-thickness ratio two-dimensional expanded graphite is used as a thermally conductive filler. The expanded graphite is first added to the semi-crystalline, non-flame-retardant EVA resin to prepare a dual-continuous phase PVC / EVA functional material with the advantages of high thermal conductivity and good flame retardant properties. When the volume content of graphite is 25%, the oxygen index of the dual-continuous phase PVC / EVA functional material prepared by the above-mentioned feeding method is greater than 35%, the smoke density level is 44.9-48.8%, the maximum smoke density is 70.7-81.3%, and the vertical combustion test is V-0 level; the thermal conductivity of the isotropic composite material when the graphite is randomly distributed is as high as 5.28-6.27W·m -1 ·K -1 The in-plane thermal conductivity of the anisotropic composite material when the graphite is oriented and distributed under shear force is 3.23~3.88W·m -1 ·K -1 、Out-of-plane thermal conductivity 7.07~8.23W·m -1 ·K -1 The mechanical properties of the dual-continuous phase PVC / EVA functional material directly prepared by the method, especially by adding a small amount of the third polymer component for compatibilization, are improved, such as tensile strength of 18.4-30.6MPa, flexural strength of 25.4-42.6MPa, flexural modulus of 2396-4663MPa, and cantilever beam notched impact strength of 3.1-7.0kJ / m 2 The dual-continuous phase PVC / EVA composite material prepared by the method of first adding high-purity expanded graphite to EVA resin and then blending with PVC resin has a comprehensive performance much better than other blending methods, and the prepared functional material can be used in occasions requiring high thermal conductivity, flame retardancy, low smoke and good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of the structure of PVC / EVA co-continuous phase blends.

[0036] Figure 2 Diagram of the isotropic thermal conductivity mechanism of PVC / EVA dual-continuous phase composite material constructed by pre-dispersing expanded graphite in EVA resin.

[0037] Figure 3 Diagram of the anisotropic thermal conductivity mechanism of PVC / EVA dual-continuous phase composite material constructed by pre-dispersing expanded graphite in EVA resin: (a) in-plane heat conduction mechanism; (b) out-of-plane heat conduction mechanism.

[0038] Figure 4 Scanning electron microscope photos of the brittle fracture surfaces of some embodiments: (a) Example 1: the graphite is isotropically arranged, (b) Example 3: the graphite is isotropically arranged, (c) Example 4: the graphite is isotropically arranged, (d) Example 5: the graphite isotropically arranged, (e) Example 6: the graphite isotropically arranged, and (f) Example 8: the graphite isotropically arranged.

[0039] Figure 5 Scanning electron microscope photographs of the brittle fracture surfaces of the comparative examples: (a) Comparative example 1 has no graphite, (b) Comparative example 2 has no graphite, (c) Comparative example 3 has anisotropic arrangement of graphite (in-plane), (d) Comparative example 4 has anisotropic arrangement of graphite (in-plane), (e) Comparative example 5 has anisotropic arrangement of graphite (in-plane), (f) Comparative example 6 has anisotropic arrangement of graphite (in-plane). DETAILED DESCRIPTION

[0040] The present invention is described below by means of specific examples, but the present invention is not limited to these examples.

[0041] Example 1

[0042] Raw material formula

[0043] 1. PVC mixture (mass ratio, parts): PVC resin (DP=1000) 100, organic tin stabilizer 1, calcium stearate 1, acrylic acid ester processing aid 1, polyethylene wax 1.

[0044] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 40, EVA random copolymer resin (VAc mass percentage 15%, MFR tested at 190℃×2.16kg is 20g / 10min) 35, expanded graphite (carbon mass percentage 99.5%, sheet thickness 0.2μm, sheet length 20μm, expansion volume 250mL / g, specific surface area 30m 2 / g)25.

[0045] Preparation process: EVA resin is first melt-blended and granulated with graphite and then blended and granulated with PVC mixture.

[0046] a. Premixing EVA and graphite: First, add powdered EVA resin and expanded graphite into a low-speed mixer and mix for 5 minutes to obtain a premix of EVA and graphite. The material temperature is controlled at 35-38°C and the speed is 350rpm during the entire mixing process.

[0047] b. EVA / graphite composite material melt blending: Parallel twin-screw extruder underwater pelletizing process pelletizing molding control conditions: zone 1 temperature 120℃, zone 2 temperature 135℃, zone 3 temperature 150℃, zone 4 temperature 160℃, zone 5 temperature 150℃, die head temperature 200℃; circulating water temperature 55℃.

[0048] c. Preparation of PVC mixture and premixing with EVA / graphite composite material: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 450rpm for 2 minutes. Start high-speed 900rpm mixing until the temperature reaches 90°C, add acrylic processing aids, continue mixing and heat to 100°C, add polyethylene wax and mix for another 2 minutes, then discharge into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 60°C, add EVA / graphite composite material pellets, continue mixing until the temperature reaches 45°C and discharge into the storage bin.

[0049] d. Preparation of dual-continuous phase PVC / EVA functional composite materials: Parallel twin-screw extruder water-cooled strand pelletizing process pelletizing molding control conditions: Zone 1 temperature 155°C, Zone 2 temperature 165°C, Zone 3 temperature 175°C, Zone 4 temperature 18°C, Zone 5 temperature 185°C, Zone 6 temperature 175°C, die head temperature 165°C; main engine screw speed 40rpm, feed speed 20rpm, pelletizing speed 200rpm. The performance is shown in Table 1.

[0050] Example 2

[0051] Raw material formula

[0052] 1. PVC mixture (mass ratio, parts): PVC resin (DP=1000) 50, PVC resin (DP=1300) 50, organic tin stabilizer 1.5, calcium stearate 1.5, acrylic acid ester processing aid 1.5, polyethylene wax 1.5.

[0053] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 35, EVA block resin (VAc mass percentage 10%, MFR tested under 190℃×2.16kg conditions is 18g / 10min) 40, expanded graphite (carbon mass percentage 99.5%, sheet thickness 0.2μm, sheet length 25μm, expansion volume 300mL / g, specific surface area 30m 2 / g)25.

[0054] Preparation process: EVA resin is first melt-blended and granulated with graphite and then blended and granulated with PVC mixture.

[0055] a. Premixing EVA and graphite: First, add powdered EVA resin and expanded graphite into a low-speed mixer and mix for 5 minutes to obtain a premix of EVA and graphite. The material temperature is controlled at 32-35°C and the speed is 400rpm during the entire mixing process.

[0056] b. EVA / graphite composite material melt blending: Parallel twin-screw extruder underwater pelletizing process pelletizing control conditions: zone 1 temperature 110℃, zone 2 temperature 125℃, zone 3 temperature 140℃, zone 4 temperature 150℃, zone 5 temperature 140℃, die head temperature 190℃; circulating water temperature 50℃.

[0057] c. Preparation of PVC mixture and premixing with EVA / graphite composite material: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 450rpm for 2 minutes. Start high-speed 900rpm and mix until the temperature reaches 90°C. Add acrylic processing aids. Continue mixing and heat to 100°C. Add polyethylene wax and mix for another 3 minutes. Then discharge the material into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 60°C, add EVA / graphite composite material pellets, continue mixing until the temperature reaches 35°C and discharge into the storage bin.

[0058] d. Preparation of dual-continuous phase PVC / EVA functional composite materials: Parallel twin-screw extruder water-cooled strand pelletizing process pelletizing molding control conditions: Zone 1 temperature 150°C, Zone 2 temperature 16°C, Zone 3 temperature 170°C, Zone 4 temperature 180°C, Zone 5 temperature 180°C, Zone 6 temperature 170°C, die head temperature 160°C; main engine screw speed 40rpm, feed speed 20rpm, pelletizing speed 200rpm. The performance is shown in Table 1.

[0059] Example 3

[0060] Raw material formula

[0061] 1. PVC mixture (mass ratio, parts): PVC resin (DP=1000) 70, PVC resin (DP=1300) 30, organic tin stabilizer 2, calcium stearate 1, acrylic acid ester processing aid 0.5, polyethylene wax 0.5.

[0062] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 37.5, EVA block copolymer resin (VAc mass percentage 20%, MFR tested at 190℃×2.16kg is 15g / 10min) 33.5, CPE resin (chlorine atomic mass percentage 30%, melting heat 15J / g, MFR tested at 190℃×2.16kg is 40g / 10min) 4, expanded graphite (carbon mass percentage 99.8%, sheet thickness 0.1μm, sheet length 30μm, expansion volume 250mL / g, specific surface area 25m 2 / g)25.

[0063] Preparation process: EVA resin is first melt-blended and granulated with graphite and then blended and granulated with PVC mixture.

[0064] a. Premixing EVA and graphite: First add powdered EVA resin and CPE resin as a compatibilizer into a low-speed mixer, start the low-speed mixer and mix for 2 minutes at room temperature, add expanded graphite and continue mixing for 5 minutes to obtain the EVA and graphite premix. The material temperature is controlled at 33-36°C and the speed is 300rpm during the entire mixing process.

[0065] b. EVA / graphite composite material melt blending: Parallel twin-screw extruder underwater pelletizing process pelletizing control conditions: zone 1 temperature 130℃, zone 2 temperature 145℃, zone 3 temperature 160℃, zone 4 temperature 170℃, zone 5 temperature 160℃, die head temperature 210℃; circulating water temperature 60℃.

[0066] c. Preparation of PVC mixture and premixing with EVA / graphite composite material: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 400rpm for 2 minutes. Start high-speed 900rpm and mix until the temperature reaches 90℃, then add acrylic processing aids. Continue mixing and heat to 100℃, add polyethylene wax and mix for another 2 minutes, then discharge into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 60℃, add EVA / graphite composite material pellets, continue mixing until the temperature reaches 40℃, and discharge into the storage bin.

[0067] d. Preparation of dual-continuous phase PVC / EVA functional composite materials: Parallel twin-screw extruder water-cooled strand pelletizing process pelletizing molding control conditions: Zone 1 temperature 145°C, Zone 2 temperature 145°C, Zone 3 temperature 165°C, Zone 4 temperature 175°C, Zone 5 temperature 175°C, Zone 6 temperature 165°C, die head temperature 165°C; main engine screw speed 40rpm, feed speed 20rpm, pelletizing speed 200rpm. The performance is shown in Table 1.

[0068] Example 4

[0069] Raw material formula

[0070] 1. PVC mixture (mass ratio, parts): PVC resin (DP=1000) 90, PVC resin (DP=1300) 10, organic tin stabilizer 1.2, calcium stearate 1.5, acrylic acid ester processing aid 1, polyethylene wax 0.8.

[0071] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 37.5, EVA block copolymer resin (VAc mass percentage 5%, MFR tested at 190℃×2.16kg is 10g / 10min) 30, CPE resin (chlorine atomic mass percentage 40%, melting heat 25J / g, MFR tested at 190℃×2.16kg is 30g / 10min) 7.5, expanded graphite (carbon mass percentage 99.8%, sheet thickness 0.1μm, sheet length 30μm, expansion volume 250mL / g, specific surface area 25m 2 / g)25.

[0072] Preparation process: EVA resin is first melt-blended and granulated with graphite and then blended and granulated with PVC mixture.

[0073] a. Premixing EVA and graphite: First add powdered EVA resin, compatibilizer CPE and resin into a low-speed mixer, start the low-speed mixer and mix for 3 minutes at room temperature, add expanded graphite and continue mixing for 6 minutes to obtain the EVA and graphite premix. The material temperature is controlled at 35-38°C and the speed is 330rpm during the entire mixing process.

[0074] b. EVA / graphite composite material melt blending: Parallel twin-screw extruder underwater pelletizing process pelletizing control conditions: zone 1 temperature 115℃, zone 2 temperature 130℃, zone 3 temperature 145℃, zone 4 temperature 155℃, zone 5 temperature 145℃, die head temperature 195℃; circulating water temperature 55℃.

[0075] c. Preparation of PVC mixture and premixing with EVA / graphite composite material: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 450rpm for 2 minutes. Start high-speed 950rpm mixing until the temperature reaches 90℃, add acrylic processing aids, continue mixing and heat to 100℃, add polyethylene wax and mix for another 3 minutes, then discharge into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 60℃, add EVA / graphite composite material pellets, continue mixing until 40℃ and discharge into the storage bin.

[0076] d. Preparation of dual-continuous phase PVC / EVA functional composite materials: Parallel twin-screw extruder water-cooled strand pelletizing process pelletizing molding control conditions: Zone 1 temperature 150°C, Zone 2 temperature 160°C, Zone 3 temperature 170°C, Zone 4 temperature 180°C, Zone 5 temperature 180°C, Zone 6 temperature 170°C, die head temperature 160°C; main engine screw speed 35rpm, feed speed 18rpm, pelletizing speed 190rpm. The performance is shown in Table 1.

[0077] Example 5

[0078] Raw material formula

[0079] 1. PVC mixture (mass ratio, parts): PVC resin (DP=1000) 100, organic tin stabilizer 1, calcium stearate 2, acrylic acid ester processing aid 2, polyethylene wax 1.

[0080] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 33, EVA block copolymer resin (VAc mass percentage 18%, MFR tested at 190℃×2.16kg is 12g / 10min) 36, VC-co-VAc binary copolymer resin (VAc mass percentage 20%, DP=400) 6, expanded graphite (carbon mass percentage 99.5%, sheet thickness 0.2μm, sheet length 25μm, expansion volume 300mL / g, specific surface area 30m 2 / g)25.

[0081] Preparation process: EVA resin is first melt-blended and granulated with graphite and then blended and granulated with PVC mixture.

[0082] a. Premixing EVA and graphite: First, add powdered EVA resin and compatibilizer VC-co-VAc resin into a low-speed mixer, start the low-speed mixer and mix for 3 minutes at room temperature, add expanded graphite and continue mixing for 5 minutes to obtain the EVA and graphite premix. The material temperature is controlled at 35-38°C and the speed is 380rpm during the entire mixing process.

[0083] b. EVA / graphite composite material melt blending: Parallel twin-screw extruder underwater pelletizing process pelletizing control conditions: zone 1 temperature 130℃, zone 2 temperature 145℃, zone 3 temperature 160℃, zone 4 temperature 170℃, zone 5 temperature 160℃, die head temperature 210℃; circulating water temperature 60℃.

[0084] c. Preparation of PVC mixture and premixing with EVA / graphite composite material: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 450rpm for 2 minutes. Start high-speed 900rpm mixing until the temperature reaches 90°C, add acrylic processing aids, continue mixing and heat to 100°C, add polyethylene wax and mix for another 2 minutes, then discharge into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 60°C, add EVA / graphite composite material pellets, continue mixing until the temperature reaches 35°C and discharge into the storage bin.

[0085] d. Preparation of dual-continuous phase PVC / EVA functional composite materials: Parallel twin-screw extruder water-cooled strand pelletizing process pelletizing molding control conditions: Zone 1 temperature 150°C, Zone 2 temperature 160°C, Zone 3 temperature 170°C, Zone 4 temperature 180°C, Zone 5 temperature 180°C, Zone 6 temperature 170°C, die head temperature 160°C; main engine screw speed 45rpm, feed speed 22rpm, pelletizing speed 210rpm. The performance is shown in Table 1.

[0086] Example 6

[0087] Raw material formula

[0088] 1. PVC mixture (mass ratio, parts): PVC resin (DP=1000) 65, PVC resin (DP=1300) 35, organic tin stabilizer 1.5, calcium stearate 0.8, acrylic acid ester processing aid 1.2, polyethylene wax 1.5.

[0089] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 30, EVA block copolymer resin (VAc mass percentage 14%, MFR tested at 190℃×2.16kg is 16g / 10min) 37.5, CPE resin (chlorine atomic mass percentage 35%, melting heat 20J / g, MFR tested at 190℃×2.16kg is 35g / 10min) 3, VC-co-VAc binary copolymer resin (VAc mass percentage 15%, DP=600) 4.5, expanded graphite (carbon mass percentage 99.5%, sheet thickness 0.15μm, sheet length 20μm, expansion volume 280mL / g, specific surface area 26m 2 / g)25.

[0090] Preparation process: EVA resin is first melt-blended and granulated with graphite and then blended and granulated with PVC mixture.

[0091] a. Premixing EVA and graphite: First, add powdered EVA resin, compatibilizer CPE and VC-co-VAc resin into a low-speed mixer, start the low-speed mixer and mix for 2 minutes at room temperature, add expanded graphite and continue mixing for 6 minutes to obtain the EVA and graphite premix. The material temperature is controlled at 32-36°C and the speed is 400rpm during the entire mixing process.

[0092] b. EVA / graphite composite material melt blending: Parallel twin-screw extruder underwater pelletizing process pelletizing control conditions: zone 1 temperature 125℃, zone 2 temperature 140℃, zone 3 temperature 155℃, zone 4 temperature 165℃, zone 5 temperature 155℃, die head temperature 205℃; circulating water temperature 60℃.

[0093] c. Preparation of PVC mixture and premixing with EVA / graphite composite material: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 450rpm for 2 minutes. Start high-speed 950rpm mixing until the temperature reaches 90℃, add acrylic processing aids, continue mixing and heat to 100℃, add polyethylene wax and mix for another 3 minutes, then discharge into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 60℃, add EVA / graphite composite material pellets, continue mixing until 40℃ and discharge into the storage bin.

[0094] d. Preparation of dual-continuous phase PVC / EVA functional composite materials: Parallel twin-screw extruder water-cooled strand pelletizing process pelletizing molding control conditions: Zone 1 temperature 155°C, Zone 2 temperature 165°C, Zone 3 temperature 175°C, Zone 4 temperature 185°C, Zone 5 temperature 185°C, Zone 6 temperature 175°C, die head temperature 165°C; main engine screw speed 40rpm, feed speed 20rpm, pelletizing speed 200rpm. The performance is shown in Table 1.

[0095] Example 7

[0096] Raw material formula

[0097] 1. PVC mixture (mass ratio, parts): 50 parts of PVC resin (DP=1000), 50 parts of PVC resin (DP=1300), 1.5 parts of organic tin stabilizer, 0.5 parts of calcium stearate, 1 part of acrylic acid processing aid, and 1 part of polyethylene wax.

[0098] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 35, EVA block copolymer resin (VAc mass percentage 10%, MFR tested at 190℃×2.16kg is 18g / 10min) 32.5, CPE resin (chlorine atomic mass percentage 35%, melting heat 25J / g, MFR tested at 190℃×2.16kg is 30g / 10min) 2.5, VC-co-VAc binary copolymer resin (VAc mass percentage 30%, DP=600) 2.5, ethylene-vinyl acetate-carbon monoxide terpolymer 2.5, expanded graphite (carbon mass percentage 99.6%, sheet thickness 0.1μm, sheet length 20μm, expansion volume 250mL / g, specific surface area 25m 2 / g)25.

[0099] Preparation process: EVA resin is first melt-blended and granulated with graphite and then blended and granulated with PVC mixture.

[0100] a. Premixing EVA and graphite: First add powdered EVA resin and CPE, VC-co-VAc, ethylene-vinyl acetate-polar monomer terpolymer and other compatibilizers into a low-speed mixer, start the low-speed mixer and mix for 3 minutes at room temperature, add expanded graphite and continue mixing for 6 minutes to obtain EVA and graphite premix. The material temperature is controlled at 35-38°C and the speed is 420rpm during the entire mixing process.

[0101] b. EVA / graphite composite material melt blending: Parallel twin-screw extruder underwater pelletizing process pelletizing control conditions: zone 1 temperature 110℃, zone 2 temperature 125℃, zone 3 temperature 140℃, zone 4 temperature 150℃, zone 5 temperature 140℃, die head temperature 190℃; circulating water temperature 50℃.

[0102] c. Preparation of PVC mixture and premixing with EVA / graphite composite material: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 450rpm for 2 minutes. Start high-speed 900rpm mixing until the temperature reaches 90°C, add acrylic processing aids, continue mixing and heat to 100°C, add polyethylene wax and mix for another 2 minutes, then discharge into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 60°C, add EVA / graphite composite material pellets, continue mixing until the temperature reaches 45°C and discharge into the storage bin.

[0103] d. Preparation of dual-continuous phase PVC / EVA functional composite materials: Parallel twin-screw extruder water-cooled strand pelletizing process pelletizing molding control conditions: Zone 1 temperature 155°C, Zone 2 temperature 165°C, Zone 3 temperature 175°C, Zone 4 temperature 185°C, Zone 5 temperature 185°C, Zone 6 temperature 175°C, die head temperature 165°C; main engine screw speed 42rpm, feed speed 22rpm, pelletizing speed 200rpm. The performance is shown in Table 1.

[0104] Example 8

[0105] Raw material formula

[0106] 1. PVC mixture (mass ratio, parts): PVC resin (DP=1000) 80, PVC resin (DP=1300) 20, organic tin stabilizer 0.5, calcium stearate 2, acrylic acid ester processing aid 1.5, polyethylene wax 1.

[0107] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 37.5, EVA block copolymer resin (VAc mass percentage 5%, MFR tested at 190℃×2.16kg is 10g / 10min) 30, ethylene-vinyl acetate-acrylate terpolymer 7.5, expanded graphite (carbon mass percentage 99.5%, sheet thickness 0.15μm, sheet length 20μm, expansion volume 280mL / g, specific surface area 26m 2 / g)25.

[0108] Preparation process: EVA resin is first melt-blended and granulated with graphite and then blended and granulated with PVC mixture.

[0109] a. Premixing EVA and graphite: First, add powdered EVA resin and ethylene-vinyl acetate-polar monomer terpolymer as a compatibilizer into a low-speed mixer, start the low-speed mixer and mix for 2 minutes at room temperature, add expanded graphite and continue mixing for 5 minutes to obtain the EVA and graphite premix. The material temperature is controlled at 33-37°C and the speed is 280rpm during the entire mixing process.

[0110] b. EVA / graphite composite material melt blending: Parallel twin-screw extruder underwater pelletizing process pelletizing molding control conditions: zone 1 temperature 120℃, zone 2 temperature 135℃, zone 3 temperature 150℃, zone 4 temperature 160℃, zone 5 temperature 150℃, die head temperature 200℃; circulating water temperature 60℃.

[0111] c. Preparation of PVC mixture and premixing with EVA / graphite composite material: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 400rpm for 2 minutes. Start high-speed 900rpm and mix until the temperature reaches 90°C. Add acrylic processing aids. Continue mixing and heat to 100°C. Add polyethylene wax and mix for another 3 minutes. Then discharge the material into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 60°C, add EVA / graphite composite material pellets and continue mixing until the temperature reaches 45°C. Discharge the material into the storage bin.

[0112] d. Preparation of dual-continuous phase PVC / EVA functional composite materials: Parallel twin-screw extruder water-cooled strand pelletizing process pelletizing molding control conditions: Zone 1 temperature 150°C, Zone 2 temperature 160°C, Zone 3 temperature 170°C, Zone 4 temperature 180°C, Zone 5 temperature 180°C, Zone 6 temperature 170°C, die head temperature 160°C; main engine screw speed 40rpm, feed speed 20rpm, pelletizing speed 200rpm. The performance is shown in Table 1.

[0113] Comparative Example 1

[0114] Raw material formula (mass ratio, parts): PVC resin (DP=1000) 100, organic tin stabilizer 1, calcium stearate

[0115] 1. Acrylate processing aid 1. Polyethylene wax 1.

[0116] Preparation process: PVC resin and additives are pre-mixed evenly and then directly granulated.

[0117] a. Preparation of PVC mixture: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 400-450rpm for 2 minutes, start high-speed 900-950rpm and mix until the temperature reaches 90℃, then add acrylic processing aids, continue mixing and heat to 100℃, add polyethylene wax and mix for another 2-3 minutes, then discharge into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 40℃, discharge it into the storage bin.

[0118] b. PVC mixture melt granulation: Use conical twin-screw extruder to granulate by air-cooled grinding surface hot cutting. The granules are cooled by 3-stage cyclone separator and then further separated by vibrating screen before entering the silo. Conical twin-screw extruder granulation molding control conditions: Zone 1 temperature 150℃, Zone 2 temperature 160℃, Zone 3 temperature 170℃, Zone 4 temperature 180℃, Zone 5 temperature 180℃, Zone 6 temperature 170℃, and die head temperature 170℃.

[0119] The performance after testing is shown in Table 2.

[0120] Comparative Example 2

[0121] Raw material formula (mass ratio, parts): EVA random copolymer resin (VAc mass percentage 18%, MFR tested under 190℃×2.16kg conditions is 3g / 10min) 100.

[0122] Preparation process: The EVA resin of comparative sample 2 is pelletized and directly injection molded into standard specimens for testing.

[0123] The performance after testing is shown in Table 2.

[0124] Comparative Example 3

[0125] Raw material formula

[0126] 1. PVC mixture (mass ratio, parts): PVC resin (DP=800) 100, organic tin stabilizer 1, calcium stearate 1, acrylic acid ester processing aid 1, polyethylene wax 1.

[0127] 2. PVC / graphite composite material (volume ratio, parts): PVC mixture 75, expanded graphite (carbon mass percentage 99.5%, sheet thickness 0.5μm, sheet length 20μm, expansion volume 250mL / g, specific surface area 25m 2 / g)25.

[0128] Preparation process: PVC resin, additives and graphite are pre-mixed evenly and then directly granulated.

[0129] a. Premixing of PVC and graphite: Add PVC resin, organic tin stabilizer, and calcium stearate to a 200L high-speed mixer and mix at a low speed of 400rpm for 2 minutes. Start mixing at a high speed of 900rpm until the temperature reaches 90°C, add acrylic processing aids and expanded graphite, continue mixing and heat to 100°C, add polyethylene wax, and mix for another 2-3 minutes. Then discharge the material into a 500L low-speed mixer with a jacket and circulating cooling water. When the material cools to 40°C, discharge it into the storage bin.

[0130] b. PVC / graphite composite material melt granulation: a conical twin-screw extruder is used to granulate by air-cooled grinding surface hot cutting. The granules are cooled by a three-stage cyclone separator and then further separated by a vibrating screen before entering the silo. The control conditions for granulation molding of the conical twin-screw extruder are: zone 1 temperature 150℃, zone 2 temperature 160℃, zone 3 temperature 170℃, zone 4 temperature 180℃, zone 5 temperature 180℃, zone 6 temperature 170℃, and die head temperature 170℃. The performance is shown in Table 2.

[0131] Comparative Example 4

[0132] Raw material formula (volume ratio, parts): EVA random copolymer resin (VAc mass percentage 18%, MFR tested at 190℃×2.16kg is 3g / 10min) 75, expanded graphite (carbon mass percentage 99.5%, sheet thickness 0.5μm, sheet length 20μm, expansion volume 250mL / g, specific surface area 25m 2 / g)25.

[0133] Preparation process: EVA resin and graphite are pre-mixed evenly and then directly granulated.

[0134] a. Premixing EVA and graphite: First, add powdered EVA resin and expanded graphite into a low-speed mixer and mix for 5 to 6 minutes to obtain a premix of EVA and graphite. The material temperature is controlled at 35 to 40°C and the speed is 400 rpm during the entire mixing process.

[0135] b. EVA / graphite composite material melt blending: parallel twin-screw extruder underwater pelletizing process pelletizing molding control conditions: zone 1 temperature 120℃, zone 2 temperature 135℃, zone 3 temperature 150℃, zone 4 temperature 160℃, zone 5 temperature 150℃, die head temperature 200℃; circulating water temperature 55±5℃. The performance is shown in Table 2.

[0136] Comparative Example 5

[0137] Raw material formula

[0138] 1. PVC mixture (mass ratio, parts): PVC resin (DP=1000) 100, organic tin stabilizer 1, calcium stearate 1, acrylic acid ester processing aid 1, polyethylene wax 1.

[0139] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 37.5, EVA random copolymer resin (VAc mass percentage 13%, MFR tested at 190℃×2.16kg is 3g / 10min) 37.5, expanded graphite (carbon mass percentage 99.5%, sheet thickness 0.5μm, sheet length 20μm, expansion volume 250mL / g, specific surface area 25m 2 / g)25.

[0140] Preparation process: PVC resin, EVA resin and graphite are pre-mixed evenly and then blended and granulated.

[0141] a. Preparation of PVC mixture and premixing with EVA and graphite powder: Add PVC resin, organic tin stabilizer and calcium stearate to a 200L high-speed mixer and mix at a low speed of 400rpm for 2 minutes. Start high-speed 900rpm and mix until the temperature reaches 90℃, then add acrylic processing aids. Continue mixing and heat to 100℃, then add polyethylene wax and mix for another 2 minutes, then discharge into a 500L low-speed mixer with jacket circulating cooling water. When the material cools to 60℃, add EVA resin and graphite powder, continue mixing until the temperature reaches 40℃ and discharge into the storage bin.

[0142] b. Preparation of dual-continuous phase PVC / EVA functional composite materials: The granulation molding control conditions of the water-cooled strand pelletizing process of the parallel twin-screw extruder are as follows: the temperature of zone 1 is 150℃, the temperature of zone 2 is 160℃, the temperature of zone 3 is 170℃, the temperature of zone 4 is 180℃, the temperature of zone 5 is 180℃, the temperature of zone 6 is 170℃, and the temperature of the die head is 160℃; the main screw speed is 40rpm, the feeding speed is 20rpm, and the pelletizing speed is 200rpm. The performance is shown in Table 2.

[0143] Comparative Example 6

[0144] Raw material formula

[0145] 1. PVC mixture (mass ratio, parts): PVC resin (DP=800) 100, organic tin stabilizer 1, calcium stearate 1, acrylic acid ester processing aid 1, polyethylene wax 1.

[0146] 2. PVC / EVA / graphite composite material (volume ratio, parts): PVC mixture 37.5, EVA random copolymer resin (VAc mass percentage 18%, MFR tested at 190℃×2.16kg is 3g / 10min) 37.5, expanded graphite (carbon mass percentage 99.5%, sheet thickness 0.5μm, sheet length 20μm, expansion volume 250mL / g, specific surface area 25m 2 / g)25.

[0147] Preparation process: The PVC mixture is first melt-blended and granulated with graphite and then blended and granulated with EVA resin.

[0148] a. Premixing of PVC and graphite: Add PVC resin, organic tin stabilizer, and calcium stearate to a 200L high-speed mixer and mix at a low speed of 400rpm for 2 minutes. Start mixing at a high speed of 900rpm until the temperature reaches 90°C, add acrylic processing aids and expanded graphite, continue mixing and heat to 100°C, add polyethylene wax, and mix for another 2-3 minutes. Then discharge the material into a 500L low-speed mixer with a jacket and circulating cooling water. When the material cools to 40°C, discharge it into the storage bin.

[0149] b. PVC / graphite composite material melt granulation: conical twin-screw extruder is used to granulate by air-cooled grinding surface hot cutting. The granules are cooled by 3-stage cyclone separator and then further separated by vibrating screen before entering the silo. Conical twin-screw extruder granulation molding control conditions: Zone 1 temperature 150℃, Zone 2 temperature 160℃, Zone 3 temperature 170℃, Zone 4 temperature 180℃, Zone 5 temperature 180℃, Zone 6 temperature 170℃, and die head temperature 170℃.

[0150] c. Premixing of EVA powder and PVC / graphite composite material pellets: Add powdered EVA resin and PVC / graphite composite material pellets into a low-speed mixer, start the mixer and mix for 5 minutes to obtain a premix of EVA powder and PVC / graphite composite material pellets. During the entire mixing process, the material temperature is controlled not to be higher than 40°C and the speed is controlled not to be higher than 450rpm.

[0151] d. Preparation of dual-continuous phase PVC / EVA functional composite materials: Parallel twin-screw extruder water-cooled strand pelletizing process pelletizing molding control conditions: Zone 1 temperature 150°C, Zone 2 temperature 160°C, Zone 3 temperature 170°C, Zone 4 temperature 180°C, Zone 5 temperature 180°C, Zone 6 temperature 170°C, die head temperature 160°C; main engine screw speed 40rpm, feed speed 20rpm, pelletizing speed 200rpm. The performance is shown in Table 2.

[0152] Table 1 Performance Summary of Examples 1 to 8

[0153]

[0154] Table 2 Performance Summary of Comparative Examples 1 to 6

[0155]

Claims

1. A thermally conductive flame-retardant composite material having a dual-continuous phase structure, characterized in that: The invention is made of the following raw materials in volume ratio: 30-40 parts of polyvinyl chloride mixture, 30-40 parts of ethylene-vinyl acetate binary copolymer, 25 parts of graphite, 0-7.5 parts of chlorinated polyethylene resin, 0-7.5 parts of vinyl chloride-vinyl acetate binary copolymer, and 0-7.5 parts of ethylene-vinyl acetate-polar monomer terpolymer; wherein the polyvinyl chloride mixture is made of the following raw materials in mass ratio: 100 parts of polyvinyl chloride resin, 0.5-2 parts of organic tin stabilizer, 0.5-2 parts of calcium stearate, 0.5-2 parts of acrylic acid ester processing aid, and 0.5-1.5 parts of polyethylene wax. The resin is a powdered resin with an average degree of polymerization of 1000 or a powdered resin of 1000 and 1300 synthesized by a suspension polymerization process, wherein the mass proportion of the polyvinyl chloride resin with an average degree of polymerization of 1300 does not exceed 50% when combined; the ethylene-vinyl acetate binary copolymer is a random copolymer or block copolymer of ethylene and vinyl acetate with a vinyl acetate mass percentage of 5-20% and a melt mass flow rate of (190°C×2.16kg) 10-20g / 10min; the preparation method of the thermal conductive flame retardant composite material with a dual continuous phase structure comprises the following steps: Premixing of EVA and graphite: Add ethylene-vinyl acetate binary copolymer, i.e. EVA, to a common low-speed mixer, and then add chlorinated polyethylene resin, i.e. CPE, vinyl chloride-vinyl acetate binary copolymer, i.e. VC-co-VAc, or ethylene-vinyl acetate-polar monomer terpolymer according to the proportion, start the low-speed mixer and mix at room temperature for 2-3 minutes, add graphite and continue mixing for 5-6 minutes to obtain the EVA and graphite premix, wherein the material temperature is controlled not higher than 40°C and the speed is controlled not higher than 450rpm during the whole mixing process; EVA / graphite composite melt blending: EVA and graphite premixes were pelletized by underwater pelletizing in a parallel twin-screw extruder to prepare EVA / graphite composite pellets, wherein the screw diameter was 65 mm and the screw aspect ratio L / D was 32:1; twin-screw extruder pelletizing molding control conditions: zone 1 temperature 120±10℃, zone 2 temperature 135±10℃, zone 3 temperature 150±10℃, zone 4 temperature 160±10℃, zone 5 temperature 150±10℃, die head temperature 200±10℃; circulating water temperature 55±5℃; Preparation of polyvinyl chloride mixture and premixing with EVA / graphite composite material: add PVC resin, organic tin stabilizer and calcium stearate to a high-speed mixer and mix at a low speed of 400-450rpm for more than 2 minutes, start high-speed 900-950rpm to mix until the temperature reaches 90°C, add acrylate processing aid, continue mixing and heat to 100°C of the polyvinyl chloride mixture, add polyethylene wax and mix for another 2-3 minutes, and then discharge the material into a low-speed mixer with jacket circulating cooling water; when the material is cooled to 60°C, add EVA / graphite composite material pellets, continue mixing until the temperature reaches 40±5°C and discharge the material into a storage bin; Preparation of thermally conductive flame-retardant composite materials with a dual-continuous phase structure: the materials in the storage bin are processed by a parallel co-rotating twin-screw extruder with a screw diameter of 65 mm and an aspect ratio of 36:1, including blending, underwater drawing and pelletizing, to obtain a thermally conductive flame-retardant composite material with a dual-continuous phase structure; the extruder granulation molding control conditions are: zone 1 temperature 150±5℃, zone 2 temperature 160±5℃, zone 3 temperature 170±5℃, zone 4 temperature 180±5℃, zone 5 temperature 180±5℃, zone 6 temperature 170±5℃, head temperature 160±5℃; main engine screw speed 40±5rpm, feeding speed 20±2rpm, pelletizing speed 200±10rpm.

2. The thermally conductive flame-retardant composite material with a dual-continuous phase structure according to claim 1, characterized in that: The ethylene-vinyl acetate binary copolymer is a powdery ethylene-vinyl acetate binary block copolymer.

3. The thermally conductive flame-retardant composite material with a dual-continuous phase structure according to claim 1, characterized in that: The graphite is high-purity expanded graphite, and the carbon mass percentage of the high-purity expanded graphite is 99.5% or more, the sheet thickness is 0.1-0.2 μm, the sheet length is 20-30 μm, the expansion volume is 250-300 mL / g, and the specific surface area is 25-30 m 2 / g.

4. The thermally conductive flame-retardant composite material with a dual-continuous phase structure according to claim 1, characterized in that: The chlorinated polyethylene resin is a high-fluidity variety with a chlorine atomic mass percentage of 30-40%, a melting heat of 15-25 J / g, and a melt mass flow rate (190°C×2.16kg) of 30-40 g / 10min. The amount of the chlorinated polyethylene resin used is 2.5-7.5 parts.

5. The thermally conductive flame-retardant composite material with a dual-continuous phase structure according to claim 1, characterized in that: The vinyl chloride-vinyl acetate binary copolymer is a copolymer prepared by a suspension process with a VAc mass percentage of 15-30% and an average polymerization degree of 400-600. The amount of the vinyl chloride-vinyl acetate binary copolymer is 2.5-7.5 parts.

6. The thermally conductive flame-retardant composite material with a dual-continuous phase structure according to claim 1, characterized in that: The ethylene-vinyl acetate-polar monomer terpolymer is an ethylene-vinyl acetate-carbon monoxide terpolymer and an ethylene-vinyl acetate-acrylate terpolymer, and the usage amount thereof is 2.5-7.5 parts.

7. A method for preparing a thermally conductive flame-retardant composite material having a dual-continuous phase structure according to any one of claims 1 to 6, characterized in that: The following steps are involved: Premixing of EVA and graphite: Add ethylene-vinyl acetate binary copolymer, i.e. EVA, to a common low-speed mixer, and then add chlorinated polyethylene resin, i.e. CPE, vinyl chloride-vinyl acetate binary copolymer, i.e. VC-co-VAc, or ethylene-vinyl acetate-polar monomer terpolymer according to the proportion, start the low-speed mixer and mix at room temperature for 2-3 minutes, add graphite and continue mixing for 5-6 minutes to obtain the EVA and graphite premix, wherein the material temperature is controlled not higher than 40°C and the speed is controlled not higher than 450rpm during the whole mixing process; EVA / graphite composite melt blending: EVA and graphite premixes were pelletized by underwater pelletizing in a parallel twin-screw extruder to prepare EVA / graphite composite pellets, wherein the screw diameter was 65 mm and the screw aspect ratio L / D was 32:1; twin-screw extruder pelletizing molding control conditions: zone 1 temperature 120±10℃, zone 2 temperature 135±10℃, zone 3 temperature 150±10℃, zone 4 temperature 160±10℃, zone 5 temperature 150±10℃, die head temperature 200±10℃; circulating water temperature 55±5℃; Preparation of polyvinyl chloride mixture and premixing with EVA / graphite composite material: add PVC resin, organic tin stabilizer and calcium stearate to a high-speed mixer and mix at a low speed of 400-450rpm for more than 2 minutes, start high-speed 900-950rpm to mix until the temperature reaches 90°C, add acrylate processing aid, continue mixing and heat to 100°C of the polyvinyl chloride mixture, add polyethylene wax and mix for another 2-3 minutes, and then discharge the material into a low-speed mixer with jacket circulating cooling water; when the material is cooled to 60°C, add EVA / graphite composite material pellets, continue mixing until the temperature reaches 40±5°C and discharge the material into a storage bin; Preparation of thermally conductive flame-retardant composite materials with a dual-continuous phase structure: the materials in the storage bin are processed by a parallel co-rotating twin-screw extruder with a screw diameter of 65 mm and an aspect ratio of 36:1, including blending, underwater drawing and pelletizing, to obtain a thermally conductive flame-retardant composite material with a dual-continuous phase structure; the extruder granulation molding control conditions are: zone 1 temperature 150±5℃, zone 2 temperature 160±5℃, zone 3 temperature 170±5℃, zone 4 temperature 180±5℃, zone 5 temperature 180±5℃, zone 6 temperature 170±5℃, head temperature 160±5℃; main engine screw speed 40±5rpm, feeding speed 20±2rpm, pelletizing speed 200±10rpm.

Citation Information

Patent Citations

  • Method for preparing conductive thermoplastic elastomer by combining prefabricated master batch and phase structure regulation

    CN111234347A

  • Graphene-reinforced hard PVC heat-conducting composite material and preparation method thereof

    CN112266549A

  • Electron beam cured intumescent coating composition

    US4014770A